2021
DOI: 10.1016/j.heliyon.2021.e07527
|View full text |Cite
|
Sign up to set email alerts
|

Why is the world not yet ready to use alternative fuel vehicles?

Abstract: Latest advantages and drawbacks of alternative fuel vehicles (AFVs) are presented. AFVs include flexible-fuel, gas, electric, hybrid, and fuel cell electric vehicles. People's knowledge and encouragement on AFVs are important for wider AFVs adoption. Several technical recommendations for increase in AFVs adoption rate are presented. This review is useful for the researchers, governments, and policymakers on AFVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 104 publications
(87 reference statements)
1
15
0
Order By: Relevance
“…The main results of this research are that knowledge of environmental issues (global or local) and the benefits of green spaces (urban and suburban) are what ultimately influence WTP, along with income (individual or family). This conclusion is in line with other studies implemented on issues other than greenery [88][89][90][91]. Further, it is found that environmental education in a general sense can contribute positively to the current demands of society because it increases knowledge about contemporary environmental issues [27,[92][93][94][95].…”
Section: Discussionsupporting
confidence: 90%
“…The main results of this research are that knowledge of environmental issues (global or local) and the benefits of green spaces (urban and suburban) are what ultimately influence WTP, along with income (individual or family). This conclusion is in line with other studies implemented on issues other than greenery [88][89][90][91]. Further, it is found that environmental education in a general sense can contribute positively to the current demands of society because it increases knowledge about contemporary environmental issues [27,[92][93][94][95].…”
Section: Discussionsupporting
confidence: 90%
“…A more general solution of acceleration is shown in eqn (8). It mainly applies to the case where the absolute value of instantaneous acceleration is greater than 3 m s −2 .…”
Section: Velocity Subset Extraction Algorithmmentioning
confidence: 99%
“…5,6 In this context, traditional fuel vehicles face great developmental challenges, and public has long criticized their fuel economy and pollutant emissions. 7,8 Severe situations such as air pollution and lack of oil provide opportunities to develop NEVs. Through a long period of technological innovation and development, EVs and HEVs have become the representatives of NEVs.…”
Section: Introductionmentioning
confidence: 99%
“…About 72% of transportation sector is used in as diesel, 23% of petrol and remaining consumption involves other alternative fuels such as LPG, CNG, Biodiesel and Ethanol etc. Estimates have specified that the total perquisitions of petroleum products in 2017-2018 was around 210MMT and out of the total demand only 17.9% was met from domestic production 14 .…”
Section: India On Alternate Fuel Resourcesmentioning
confidence: 99%